Tinjauan Perampasan Aset dalam Tindak Pidana Pencucian Uang dari Perspektif Keadilan - Fuadi, Gumilang; Putri, Windy Virdinia; Raharjo, Trisno (Universitas Muhammadiyah Yogyakarta, 2024)
Money laundering is a crime that harms the public interest, causes economic instability in a country, and is more dangerous than corruption because tracking money flow from money laundering will be more difficult. When considering the impact, asset forfeiture is vital since it employs a